DEVELOPMENT OF RESIN-BOUND REAGENTS FOR ANALYSIS OF CARBOXYLIC ACIDS AND AMINES (1993)
Resin-bound-reagents made up of ionically-bound 2- naphthalene-methanol and covalently bound and sodium-benzoxazole- 2-sulfonate have been synthesized and utilized as analytical reagents for the pre-chromatographic derivatization of fatty acids (i.e. acetic, lauric, capric, hexanoic, octanoic, nonanoic, palmitic, docosanoic linoleic), 1° and 2° aliphatic amines and amino acids respectively. The reagents have been designed to contain fluorescent moieties attached to the anionic and cationic resin backbones through sulfonated ester linkages. These moieties imparted UV and FL detector properties to the final derivatives. The derivatization reactions were performed before the thin- layer Chromatographie separations. Standards we,-e prepared and were used in monitoring the extent of reactions on the resin support. The derivatives were chromatographed and fluorescent spots were observed under UV light. These solid phase derivatizations have led to preliminary investigation of these two functionalities before embarking on instrumentation analysis such as high performance liquid chromatography with UV or fluorescence detection and HPLC-MS Identification.